PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT PEGADAIAN (PERSERO) BATAM - Mifthahul Rachmania; M. Khoiri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Employee performance at PT Pegadaian (Persero) Batam is examined in this article to see whether training and career development have a significant impact on employee performance, or if these two factors are interrelated in any way. In particular, this essay will look into whether or not employee performance at PT Pegadaian (Persero) Batam is affected by training and career development (Persero). Batam. The research was quantitative in nature, with both primary and secondary data sources utilized. For the primary data, questionnaires and a collection of statements with Likert-scale measures were distributed. In addition, 105 employees of PT Pegadaian (Persero) Batam were asked to fill out questionnaires. Because of its adaptability, the Likert scale was selected as the measurement tool. Analysis results were validated by using descriptive statistical methods, as well as checks for data quality, influence and hypothesis testing. The SPSS 25 statistical program was used by the researcher to do all of the relevant data calculations. According to the results of the t-test, both training and career development had a substantial impact on employee performance. Employee performance was also significantly influenced by the training variable. There is a correlation between employee performance and training and career advancement, but this is not a causative relationship, according to the results of the F test.